Imagining a community a reading of Alicia Magos collection of the Suguidanon (Epics) of the tumandok of Central Panay. - Subaldo, Mary Karlyn Granada (2016.)
This study dissected the motivations of Alicia Magos in hunting for the Sugidanon (epic) of the Tumandok of Central Panay in 1992. After fifteen (15) years, the University of the Philippines decided to publish the ten-volume Sugidanon in order to preserve the declining oral tradition of the Tumandok. Using Postcolonial line of thinking, this study criticized the implications of textualizing and publishing them to the involved actors: Alicia Magos, the University of the Philippines, and the Tumandok community initial results of the study show that: 1) the translated epics are merely for the consumption of the mainstream society, and did not attempt to voice out the contemporary problems and struggles of the indigenous people; 2) the translation and publication of the epics has contributed to the death and decay of the Tumandok culture; and 3) the publication of the epics has made the Sugidanon a public property; a good that can be bought. Such points will be explained further in the study.
Research Project (Undergraduate, Bachelor of Arts in Political Science-History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Magos, Alicia -- Collection -- Research; Sugidanun (Epic) -- Research; Tumandok -- Central Panay -- Research